TEKNIK MENCATAT DENGAN MIND MAP PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VIII DI MTI TARUSAN KAMANG - Hannah Fuadi; Muhiddinur Kamal; Zulfani Sesmiarni; Supratman Zakir (KOLONI, 2022)
This research is motivated by the SKI learning media which still requires an upgrade in attracting interest in learning. In the learning activities of Islamic Cultural History at MTI Tarusan, they carry out learning activities using a Mind Map where students are asked to record one sheet of paper. The purpose of this study was to find out the technique of note-taking with a Mind Map in Islamic Cultural History class VIII at MTI Tarusan Kamang. The type of research used is qualitative with research results in the form of descriptions with the meaning of describing the results of the research in the form of paragraphs, then data collection techniques using observations and interviews and documentation. Informants in this study were SKI teachers, class VIII students, and school principals. The results showed that; Taking notes with a Mind Map on Islamic Cultural History learning in class VIII, the Mind Map is considered successful because it can be seen from the results of students' work in noting that Mind Maps almost entirely meet the standard criteria in making Mind Maps, besides that it is very helpful for teachers in providing understanding of the material to students so that students understand the material. And can improve students' ability to remember material and public speaking skills, as well as students' creativity. Keywords: Mind Map, Techniques, Learning Media, and Islamic Cultural History Learning (SKI)